2010
DOI: 10.1111/j.1439-0531.2008.01294.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of RepeatedIn VivoOocyte and Embryo Recovery After rhFSH Treatment in Rabbits

Abstract: This study aims to assess the efficiency of in vivo oocyte and embryo recovery after a recombinant human FSH (rhFSH) treatment in rabbit does. Females were distributed in two experimental groups: donor does were treated with rhFSH (superovulation group) for 3 days prior to artificial insemination (embryo recovery) or ovulation induction (oocyte recovery) and does without treatment remained as the control group. Mature oocytes or embryos were collected with the laparoscopy technique 16 h after ovulation inducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Although LH has been known as the primary hormone essential for ovulation and luteinization, studies using purified FSH preparations have suggested that FSH is capable of inducing ovulation in rats and hamsters (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Additionally, studies in hypophysectomized rats using recombinant human FSH (rhFSH) have confirmed that folliculogenesis and ovulation were induced by rhFSH alone (14,15).…”
mentioning
confidence: 87%
“…Although LH has been known as the primary hormone essential for ovulation and luteinization, studies using purified FSH preparations have suggested that FSH is capable of inducing ovulation in rats and hamsters (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Additionally, studies in hypophysectomized rats using recombinant human FSH (rhFSH) have confirmed that folliculogenesis and ovulation were induced by rhFSH alone (14,15).…”
mentioning
confidence: 87%
“…Given that it has been observed that FSH in absence of LH could induce superovulatory response in rabbit does both using purified porcine FSH or recombinant human FSH Cortell et al, 2008;Viudes de Castro et al, 2009), in the present study, the effect of these hormonal preparations on ovulation rate and oocyte quality was compared. Regarding to superovulatory response, both purified pFSH administered in five injections, twice a day (pFSH5), and rhFSH dissolved in PVP administered in three injections, once a day for three days (rhFSH3), resulted in a higher ovulation rate than control group.…”
Section: Discussionmentioning
confidence: 99%
“…In rabbits, superovulation protocols have been performed widely with eCG or FSH (Kauffmann et al, 1998;Cortell et al, 2008;Viudes de Castro et al, 2009;Viudes de Castro et al, 2010). Nevertheless, the recovery efficiency and oocyte quality of these superovulation treatments are highly variables.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations